MINAT MAHASISWA AKUNTANSI FAKULTAS BISNIS UNIVERSITAS TRIATMA MULYA BERKARIR DI BIDANG PERPAJAKAN DI TINJAU DARI PERSEPSI, MOTIVASI, DAN PENGETAHUAN PERPAJAKAN - Putu Oka Linda Pradnya Wati; I Gusti Agung Krisna Lestari; Ni Made Ernila Junipisa (Universitas Triatma Mulya, 2023)
The purpose of this study is to determine the impact of tax perceptions, motivations, and knowledge on the interests of accounting students in their tax careers. The research subject consisted of students from the Faculty of Economics, Triatma Muriyah University, and her sample was 134 respondents. The data collection method is a questionnaire. The data analysis techniques used in this study are multiple regression, coefficient of determination, F-test, and t-test. Based on research results, we find that perception has a significant positive impact on accounting students' interest in tax work, while motivation has a significant positive impact on accounting students' interest in a career in this field. Tax knowledge and tax knowledge have a significant positive impact on an accounting student's interest in a career in the tax field. The magnitude of the impact of variables perception, motivation, and tax knowledge on accounting students' interest in a tax career is 62.7%. The researchers suggested that Triatoma Muriya University would organize tax seminars and provide tax courses with appropriate materials and experienced lecturers to improve awareness, motivation and knowledge in the tax field. , is expected to be able to increase interest in the tax area later. The number of accounting students pursuing careers in the tax field will increase.